Respostas
respondido por:
0
Vamos lá!
f(1) = 4 . 1 - 1 = 4 - 1 = 3
f(0) = 4 . 0 - 1 = 0 - 1 = - 1
f(1) - f(0) = 3 - (-1) = 3 + 1 = 4
Observação: o valor que tem entre parênteses (no caso o 1 e o 0) deve ser trocado a função pelo x.
Esperto ter ajudado.
f(1) = 4 . 1 - 1 = 4 - 1 = 3
f(0) = 4 . 0 - 1 = 0 - 1 = - 1
f(1) - f(0) = 3 - (-1) = 3 + 1 = 4
Observação: o valor que tem entre parênteses (no caso o 1 e o 0) deve ser trocado a função pelo x.
Esperto ter ajudado.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás